Coccidioidal Hepatic Abscess in a Patient With Disseminated Coccidioidomycosis: A Case Report - Nadia Raza MD; Faisal Nasrawi MD; Arash Heidari MD; Rasha Kuran MD; Navinchandra Amin MD; Royce Johnson MD (SAGE Publishing, 2021)
Coccidioidomycosis is an infection caused by inhalation of arthroconidia of Coccidioides . Forty percent of patients will develop mild and self-limited respiratory infection, and a small fraction of these individuals will develop extrapulmonary disseminated disease. This is the case of a patient with a known history of disseminated coccidioidomycosis, who initially presented for symptoms of persistent pneumonia. On evaluation, the patient was found to have a hepatic abscess for which he underwent percutaneous drainage. Culture grew Coccidioides immitis , and the patient was treated with systemic antifungal. This is a rare case of disseminated coccidioidomycosis in the liver.